Optimization of chest radiographic imaging parameters: a comparison of image quality and entrance skin dose for digital chest radiography systems - Sun, Zhonghua; Lin, C.; Tyan, Y.; Ng, K. (Elsevier Ltd, 2012)
We studied the performance of three computed radiography and three direct radiography systems with regard to the image noise and entrance skin dose based on a chest phantom. Images were obtained with kVp of 100, 110, and 120 and mA settings of 1, 2, 4, 8, and 10. Significant differences of image noise were found in these digital chest radiography systems (Pb<0001). Standard deviation was significantly different when the mAs were changed (Pb<001), but it was independent of the kVp values (P=.08–.85). Up to 44% of radiation dose could be saved when kVp was reduced from 120 to 100 kVp without compromising image quality.